Using Open Remote Sensing and Geographic Data for SMART Monitoring of Nature-based TOURISM in the Azores Islands Natural Parks : towards (more) Sustainability - Gil, Artur José Freire (2021)
Proceedings of the 11th International Symposium on Digital Earth (ISDE 11), Florence (Italy), September 24-27, 2019.